Optimizing the Human Resource Management Function in Improving Employee Performance in the Digital Era at PT Bahana Swara Asembagus - Yasmin Naini Bahanan; Lusi Endang Sri Darmawati; Raudatul Jannah (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the optimization of the human resource management (HRDM) function in improving employee performance in the digital era at PT Bahana Swara Asembagus, focusing on the implementation of the HRM function, optimization efforts, and obstacles faced. The research uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation, and is analyzed using data reduction, data presentation, and conclusion drawing with validity test through triangulation. The results show that the implementation of the HR function—including HR planning, training and development, and performance assessment—has been running but is still dominated by conventional approaches and has not been digitally integrated. Optimization efforts are carried out through the use of technology in work operations, improving employee digital competence, and using digital communication media, although it is still partial. The main obstacles include the limitations of technological infrastructure, low digital literacy, resistance to change, and the absence of a structured training system. This research emphasizes that optimizing human resources in the digital era requires a holistic and integrated approach between technology, human resource development, and organizational culture to improve employee performance in a sustainable manner.